Calculations for one illustration of the Pythagorean Theorem - А. А. Кореновский (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2020)
On the sides of a right-angled isosceles triangle, squares external to this triangle are built. The task is to construct a straight line on a plane that divides a figure consisting of these three squares into two equal-sized (that is, equal area) figures. Some parameters determined by this line are calculated, in particular, the areas of parts of the original squares in half-planes. The corresponding results are illustrated by various drawings, tables and graphs.